PENGARUH TINGKAT SUKU BUNGA BANK DAN NISBAH BAGI HASIL PADA DEPOSITO MUDHARABAH - Alinda, Rika Putri Nur; Riduwan, Akmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence of interest rate and nisbah of profit sharing to the mudharabah saving deposit at Bank BRI Syariah. The independent variables are the interest rate and the nisbah of profit sharing and whereas the dependent variable is the mudharabah saving deposit. The sample is Bank BRI Syariah and the observation data are 20 observations from January 2009 to September 2015. The data has been obtained from three quarter statements of Bank BRI Syariah through Indonesia Stock Exchange and Financial Statistics of Bank Indonesia. This research uses correlational research with quantitative approach. The analysis method has been done by using multiple linear regressions.The result of the research shows that (a) the interest rate does not have any influence to the mudharabah saving deposit at Bank BRI Syariah, which means that changes in interest rates do not affect mudharabah saving deposits at Bank BRI Syariah due to the fact that there is a belief that bank interest is contradicted to the religion and (b) the nisbah of profit sharing shows positive influence to the mudharabah saving deposit at Bank BRI Syariah which means that when the nisbah of profit sharing that has been given by Bank BRI Syariah to the bank customers is increasing, it will enhance the amount of mudharabah saving deposit.Keywords : Interest Rate, Nisbah of Profit Sharing, Mudharabah Saving Deposit.